Keefektifan Media Canva Materi Mitigasi Bencana Kekeringan Untuk Siswa Kelas IV Sekolah Dasar - Hidayat, Inggrid Imania; Istiq’faroh, Nurul; Syahputra , Afrizal Hadi (CV. Kurnia Grup, 2026)
This Study employs a quantitative approach using a quasi-experimental design with a one-group pretest-posttest model. The subjects of the study were 23 fourth-grade elementary school students. The research instrument consisted of 15 objective test items that had been tested for validity and reliability. Data analysis techniques included the normality test, paired sample t-test, and N-Gain calculation to determine the level of improvement in students’ learning outcomes. The results showed that the data were normally distributed and there was a significant difference between pretest and posttest scores, with a significance value of < 0.05. In addition, the N-Gain test result showed an average score of 0.8013, which falls into the high category, indicating a significant improvement in learning outcomes after the use of Canva-based digital media. Thus, it can be concluded that Canva-based digital media is effective in teaching drought disaster mitigation in elementary schools, as it enhances students’ understanding, engagement, and learning outcomes optimally.